2012
DOI: 10.13005/ojc/280302
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Decolorization Efficiency of Indigo Carmine by TiO2/UV Photocatalytic Process Coupled with Response Surface Methodology

Abstract: Experimental design methodology was applied for the optimization of indigo carmine dye photocatalytic degradation by supported TiO 2 and UV light in a flow reactor. The variables considered were the initial concentration, pH, volume of solution and recirculation flow rate. The effects of individual variables and their interaction effects for the photocatalytic degradation efficiency (%) were determined. From statistical analysis, the most effective parameters were pH and initial concentration. The optimized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…By comparing the results in Figure 8 a with those in Figure 8 b,c, we observed that an extreme initial concentration of 3000 mg·dm −3 exhibited the slowest degradation rate independent of the composite and temperature. Despite the large differences in the initial concentrations used by us and other authors [ 31 , 36 , 37 ], the effect was similar. The kinetic curves in Figure 8 a obeyed a second order rate equation, and the rate constants were 0.5 × 10 −2 for MT-G5 at 25 °C and 1.5 × 10 −2 g·mg −1 ·h −1 for MT-G50 at 50 °C.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…By comparing the results in Figure 8 a with those in Figure 8 b,c, we observed that an extreme initial concentration of 3000 mg·dm −3 exhibited the slowest degradation rate independent of the composite and temperature. Despite the large differences in the initial concentrations used by us and other authors [ 31 , 36 , 37 ], the effect was similar. The kinetic curves in Figure 8 a obeyed a second order rate equation, and the rate constants were 0.5 × 10 −2 for MT-G5 at 25 °C and 1.5 × 10 −2 g·mg −1 ·h −1 for MT-G50 at 50 °C.…”
Section: Resultssupporting
confidence: 67%
“…In addition, we decided to optimize the photodegradation of IC using the prepared TiO 2 /carbon materials. Abaamrane et al reported on the optimal decolorization of IC using TiO 2 /UV and the response surface methodology [ 37 ]. In the current work, we used the Taguchi method [ 38 ] for the evaluation of the color removal produced by IC through a small number of trials.…”
Section: Resultsmentioning
confidence: 99%
“…From an environmental point of view, the remediation of wastewater is a great challenge and has attracted tremendous attention in recent years. Different methods have been used for dye removal from wastewaters such as biological degradation [7], photodegradation [8], coagulation [9], membrane filtration [10], reverse osmosis [11], adsorption [12], or the synergic treatment using different methods. Among these methods, the adsorption process is one of the most effective techniques that has been successfully employed for colour removal because it is considered to be less expensive, more efficient and less likely to generate secondary waste [13].…”
Section: Introductionmentioning
confidence: 99%
“…In a full factorial experiment, both of the (−1) and (+1) levels of every factor are compared with each other and the effects of each of the factor levels on the response are investigated according to the levels of other factors. Doing so with the factorial planning of the experiments, it was possible to investigate simultaneously the effect of all the variables [19][20][21][22].…”
Section: Canadian Chemical Transactionsmentioning
confidence: 99%